SOSIALIALISASI ANTI NARKOBA, KEKERASAN SEKSUAL TERHADAP ANAK DAN PERUNDUNGAN DI LINGKUNGAN PENDIDIKAN, SEBAGAI IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH ISLAM NABILAH, BATAM, KEPULAUAN RIAU - Sarmini; Diana Titik Widayanti; Maizar; Arif Rahman Hakim; Kusminin; Taufik (Jurnal Pengabdian Ibnu Sina, 2023)
ABSTRACT Nabilah Islamic School, Batam, on Thursday, October 6, 2022 held a Socialization Against Drugs, Sexual Violence Against Children and Bullying in Educational Environments. In its implementation, this socialization synergizes with the Narcotics Unit of the Barelang Police, Riau Islands, and the Regional Child Protection Commission (KPPAD) of Batam City. This activity is carried out as an implementation of the Independent Curriculum and Pancasila Student Profile, where the program is in accordance with the Nabilah Islamic School as a Child Friendly School (SRA). With this socialization, it is hoped that students can find out directly from the resource person in order to understand drugs and their bad effects, prevent sexual violence against children and can minimize bullying in the educational environment. Participants who attended were from elementary, middle and high school levels as well as all teachers at the Nabilah Islamic School. This socialization aims to make students understand the bad effects of drugs, sexual violence against children and bullying in the school environment.